THE SAW-TOOTHED GRAIN BEETLE (ORYZAEPHILUS SURINAMENSIS L.) AS A PEST DAMAGING STORED AGRICULTURAL PRODUCTS (Scientific Conference on Multidisciplinary Studies, 2025)
This article provides information about the types of pests that infect replacement products during storage and the types of products that damage them.